2019
DOI: 10.3892/or.2019.7414
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of thioredoxin and its reductase attenuates arsenic trioxide‑induced growth suppression in human pulmonary artery smooth muscle cells by reducing oxidative stress

Abstract: The thioredoxin (Trx) system is an important enzymatic complex involved in cellular redox homeostasis. Arsenic trioxide (ATO; As 2 O 3) is known to trigger cell death in vascular smooth muscle cells (VSMCs) via oxidative stress. In the present study, the effects of changes in thioredoxin 1 (Trx1) and Trx reductase1 (TrxR1) on cell growth, death, reactive oxygen species (ROS), and glutathione (GSH) levels were evaluated in ATO-treated human pulmonary artery smooth muscle cells (HPASMCs). ATO inhibited growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…PX-12 is a selective Trx1 inhibitor, which has been well-used in study the function of Trx1. 55 , 56 The results in the present study showed PX-12 significantly inhibited AET-induced reduction of ROS level, ER stress and cell apoptosis, and improvement of heart function and cardiac fibrosis. These findings suggested that the cardioprotective effect of AET seemed to be linked to Trx1-regulated ER stress adaptation.…”
Section: Discussionsupporting
confidence: 51%
“…PX-12 is a selective Trx1 inhibitor, which has been well-used in study the function of Trx1. 55 , 56 The results in the present study showed PX-12 significantly inhibited AET-induced reduction of ROS level, ER stress and cell apoptosis, and improvement of heart function and cardiac fibrosis. These findings suggested that the cardioprotective effect of AET seemed to be linked to Trx1-regulated ER stress adaptation.…”
Section: Discussionsupporting
confidence: 51%
“…Overall levels of intracellular ROS including H 2 O 2 , • OH, and ONOO • were measured using a fluorescent probe dye, 2',7'-dichlorodihydrofluorescein diacetate (H 2 DCFDA, Ex/Em = 495 nm/529 nm; Invitrogen Molecular Probes, Eugene, OR, USA), as previously described 37 , 38 . H 2 DCFDA is poorly sensitive to O 2 •− .…”
Section: Methodsmentioning
confidence: 99%
“…Ex/Em = 490 nm/515 nm) as previously described (Han et al, 2008a;Han & Park, 2009a;Park, 2020b;You & Park, 2011). HPF specifically reacts with ˙OH or ONOO˙and yields a bright green-fluorescent product.…”
Section: Determination Of Intracellular Ros and O 2 ˙à Levelsmentioning
confidence: 99%